Identification of differentially expressed miRNAs and their target genes in response to brassinolide treatment on flowering of tree peony (Paeonia ostii) - Zhang, Lin; Song, Chengwei; Guo, Dalong; Guo, Lili; Hou, Xiaogai; Wang, Huafang (Plant signaling & behavior, 2022)
Tree peony is a famous flower plant in China, but the short and concentrated flowering period limits its ornamental value and economic value. Brassinolide (BR) plays an important role in plant growth and development including flowering. There have been a large number of reports on the molecular aspects of the flowering process, but the genetic mechanism that was responsible for miRNA-guided regulation of tree peony is almost unclear. In this study, the leaves of tree peony cultivar, 'Feng Dan', were sprayed with different concentrations of BR, and the obvious bloom delay was found at the treatment with BR 50 μg/L. The small RNA sequencing and transcriptome sequencing were performed on the petals of tree peony under an untreated control (CK) and the treatment with BR 50 μg/L during four consecutive flowering development stages. A total of 22 known miRNAs belonging to 12 families were identified and 84 novel miRNAs were predicted. Combined with transcriptome data, a total of 376 target genes were predicted for the 18 differentially expressed known miRNAs and 177 target genes were predicted for the 23 differentially expressed novel miRNAs. Additionally, the potential miRNAs and their target genes were identified, including miR156b targeting SPL, miR172a_4 targeting AP2 and four novel miRNAs targeting SPA1, and revealed that they might affect the flowering time in tree peony. Collectively, these results would provide a theoretical basis for further analysis of miRNA-guided regulation on flowering period in tree peony.